The Role of Intrinsic Motivation and Psychological Empowerment in the Relationship of Transformational Leadership and Employees Innovative Behavior Post COVID-19 Pandemic - Sayuti, Abdul Malik; Safitri, Denanda Agnes (Gema Wiralodra, 2024)
Innovative work behavior provides opportunities for implementing better work systems in carrying out tasks. Transformational leadership, intrinsic motivation and psychological empowerment play a role in encouraging employee innovative behavior. COVID 19 pandemic forces every employee to increase innovative behavior in facing work challenges after this era. There are two aims of this research. First one, exploring the influence of transformational leadership, intrinsic motivation and psychological empowerment on employee innovative work behavior after COVID-19 pandemic. Secondly, exploring intrinsic motivation and psychological empowerment moderating role in this relationship. Non-probability random sampling used for sample collection where the researcher determined three criterias that respondents needed to meet. The data of this research were analyzed by testing the measurement model, structural model and  testing the hypotheses using Structural Equation Modeling with SMART-PLS. The results obtained are a) Transformational leadership influences employee innovative work behavior, b) intrinsic motivation influences employee innovative work behavior, c) intrinsic motivation doesn’t moderate the relationship between transformational leadership and employee work innovative behavior, d) psychological empowerment influences employee innovative behavior, and e) psychological empowerment doesn’t moderate transformational leadership on employee innovative work behavior.